ANALISIS KELAYAKAN FINANSIAL USAHA PENANGKAPAN IKAN DENGAN KAPAL PURSE SEINE BERPENDINGIN FREEZER DIBANDINGKAN DENGAN ES DI PELABUHAN PERIKANAN PANTAI (PPP) BAJOMULYO, JUWANA, KABUPATEN PATI - Anggoro Bagus Prasetyo; Trisnani Dwi Hapsari; Indradi Setiyanto (Pena Akuatika Jurnal Ilmiah Perikanan Dan Kelautan, 2017)
Bajomulyo's Coastal Fishery Port is one of the Fishing Port located in the Province of Central Java. Purse seine is a dominant fishing gear in TPI unit II PPP Bajomulyo. Purse Seiner base in Bajomulyo use cooling system frezzer and ice. fishermen in Bajomulyo change their ice cooling system to freezer. The purposes of this research was to analyzed the business aspect of purse seiner freezer refrigeration system and ice cooling system and to analyzed the financial feasibility of purse seiner freezer refrigeration system and ice cooling system. Descriptive method with study case was used in this research. Total revenew of purse seiner with refrigeration system was Rp. 4.823.550.000/year, while the purse seiner refrigerated ice was Rp. 2.470.781.467/ year. The result of the calculation of financial analysis shows that fishing effort purse seiner refrigerated frezzer in the long run more profitable than the purse seiner refrigerated ice despite the attempt purse seine with both types of cooling systems are equally financially viable where NPV were positive, IRR was greater than the interest rate and B / C ratio was more than 1.Keywords : purse seiner; financial analysis; Fishing Port of Bajomulyo